A vortex-implanted initialization scheme for the mesoscale eddy prediction: Idealized experiments - Zhu, Yuhang; Peng, Shiqiu; Li, Yineng (Frontiers in Marine Science, 2022)
Mesoscale eddy prediction has been a big challenge to oceanographers and marine environment forecasters. Although the traditional initialization for the prediction, i.e., through assimilating the satellite-derived sea level anomalies (SLA) into a model, has some improvement, it is yet unable to predict well the main characteristics of a mesoscale eddy, including its three-dimensional (3D) structure, moving track, size, and intensity. In this study, a vortex-implanted initialization scheme for the mesoscale eddy prediction (VISTMEP) is developed. With the VISTMEP, a bogus vortex is first constructed in terms of 3D SLA-derived currents, and then it is implanted into the model initial field to obtain a more accurate 3D current field of a mesoscale eddy for prediction. The results from idealized experiments show that the VISTMEP can significantly improve prediction of the mesoscale eddy with a longer valid prediction length up to 30 days compared to the experiment with the traditional initialization. Detailed analysis indicates that, as the model is integrated forward, a more “realistic” 3D structure of the eddy in terms of both current and temperature fields is formed when the VISTMEP is employed, leading to the improvement of the eddy prediction regarding to the moving track, size, and intensity of the eddy, which is largely influenced by the accuracy of the initial current field of the eddy obtained by the VISTMEP. This study provides an innovative method for the mesoscale eddy prediction, which could have great potential application in operational services of the marine environments.